Kebijakan Kepala Sekolah Dalam Pengadaan Sarana Prasarana (Di SMP Swasta Islam Terpadu Al-Hijrah) - Rida Ramadhani Ritonga; Yusuf Hadijaya; Zulkifli Tanjung (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study generally aims to describe (1) how the principal's policy planning is in improving school facilities and infrastructure (2) how is the implementation of the principal's policy in improving school facilities and infrastructure (3) how is the evaluation of the principal's policy in improving facilities and school infrastructure. This study uses a qualitative method with a descriptive approach. The subjects in this study were students of the Al Hijrah Integrated Islamic Private Middle School, the madrasa head of the Al Hijrah Integrated Islamic Private Middle School, the teachers of the Al Hijrah Integrated Islamic Private Middle School, the KTU of the Al Hijrah Integrated Islamic Private Middle School and the student affairs department and curriculum of the Integrated Islamic Private Middle School. Al emigrated. Data collection techniques with observation, interviews and documentation. Data validation techniques with credibility, transferability, dependability and certainty. The results of this study indicate (1) Principal Policy Planning in Improving Learning Facilities and Infrastructure at SMPS IT AL HIJRAH, compiling a list of needs, estimating costs, compiling priority scales and preparing a procurement plan. (2) Implementation of the Principal's Policy in Improving Learning Facilities and Infrastructure at SMPS IT AL HIJRAH. Implementation of the principal's policy regarding facilities and infrastructure is the second step after planning in management, carrying out the procurement of facilities and infrastructure, distribution, utilization, maintenance. And (3) Evaluation of the Principal's Policy in Improving Facilities and Infrastructure and Learning Achievement at SMPS IT AL HIJRAH. a) The evaluation of facilities and infrastructure at SMPS IT AL HIJRAH is the responsibility of the principal and representatives of the facilities and infrastructure sector through supervision, b) input and processes, c) products and results of facilities and infrastructure.